The impact of active labor market programs on municipal services - Eva Mörk (Institute for Labour Market Policy Evaluation (IFAU), 2003)
Just like any other employer, the municipalities can engage participants in active labor market programs in their activities. Does this possibility affect the output of municipal services? In order to answer this question a measure for output of locally provided schooling is created using factor analysis methods. It turns out that this measure is preferable to the traditionally used variable; spending. The possibility for municipalities to engage participants in active labor market programs in their activities seems to have a negative effect on the price for schooling. Prices, in turn, have a positive impact on output of schooling. Taken together, these results indicate that participants in active labor market programs contribute to production and that these contributions are not neutralized by displacement effects.
Keywords: C23; H42; H70; 330; Local public services; factor analysis methods; active labor market programs